Accountability of local government in vietnam: in search of some theoretical aspects - Ha, Ngoc Anh (2020)
Accountability and the accountability of local government are newly-addressed issues in Vietnam, which have drawn the attention of the Communist Party, the State and the entire society of Vietnam. There have been different arguments on theoretical issues on the accountability of local government, which need to be fürther clarified. This paper focuses on reasoning out the most fundamental theoretical issues on the accountability of local government in Vietnam.